2020
DOI: 10.3390/nu12061900
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Chronotype, Adherence to the Mediterranean Diet and Sexual Opinion among University Students

Abstract: A person’s chronotype determines different habits, among which are eating and physical activity. Furthermore, at the university stage, social and organisational factors have a direct effect on students’ daily attitudes and habits. Adherence to the Mediterranean diet is linked to better sleep quality and less social jet lag, but association with chronotype or sexual opinion remains unclear. The aim of this study was to assess the associations between chronotype, adherence to the Mediterranean Diet, and sexual o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 59 publications
3
22
0
1
Order By: Relevance
“…Studies have shown that evening types have a reduced time and a low quality of sleep, daytime sleepiness and worse school performances [53]. Moreover, recent studies have shown that students with an evening chronotype had a lower adherence to the Mediterranean diet, reporting a significantly lower intake of fruits, vegetables, pulses, cereals and olive oil and higher breakfast skipping [54]. Therefore, this factor could be directly or indirectly affecting academic performance in line with this research.…”
Section: Discussionsupporting
confidence: 81%
“…Studies have shown that evening types have a reduced time and a low quality of sleep, daytime sleepiness and worse school performances [53]. Moreover, recent studies have shown that students with an evening chronotype had a lower adherence to the Mediterranean diet, reporting a significantly lower intake of fruits, vegetables, pulses, cereals and olive oil and higher breakfast skipping [54]. Therefore, this factor could be directly or indirectly affecting academic performance in line with this research.…”
Section: Discussionsupporting
confidence: 81%
“…From a health perspective, the morning chronotype has been the preferred chronotype over the evening one, with the former having less association with cardiometabolic risk factors and other health problems, including psychological, neurological, and gastrointestinal morbidities, and lower mortality rates compared to evening chronotypes (69). These health improvements associated with the morning chronotype could be also a mirror for the improved eating habits consistently reported with such chronotype, as revealed by the increased adherence to the MD by people with morning chronotype (70,71). The reported low prevalence of morningness chronotype in comparison with the eveningness one (15.1% vs. 24.5%, respectively) among the study sample is expected, considering the frequently observed long stay up at night among surrounding and neighboring students, and in line with the low prevalence reported in other parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve of the included studies had a cross-sectional design [ 10 , 12 , 18 , 20 , 21 , 22 , 23 , 24 , 26 , 27 , 29 , 30 ], one was a retrospective cohort [ 28 ] and two were case-control [ 19 , 25 ]. Six out of the fifteen studies selected were conducted in Turkey and two in Spain.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining seven studies were conducted in Italy, Hong Kong, Lebanon, France, United Kingdom, China, and Germany. The mean age of the study population ranged from 21 [ 22 ] to 9 years [ 28 ] ( Table 1 ). With regard to the quality of evidence, 6 out of the 15 selected studies were considered as ‘good’, [ 10 , 20 , 22 , 24 , 27 , 28 ], while the remaining 9 were rated ‘fair’ [ 12 , 18 , 19 , 21 , 25 , 26 , 29 , 30 ] ( Tables S2–S4 ).…”
Section: Resultsmentioning
confidence: 99%